2013
DOI: 10.1172/jci67603
|View full text |Cite
|
Sign up to set email alerts
|

NADPH oxidase 4 limits bone mass by promoting osteoclastogenesis

Abstract: ROS are implicated in bone diseases. NADPH oxidase 4 (NOX4), a constitutively active enzymatic source of ROS, may contribute to the development of such disorders. Therefore, we studied the role of NOX4 in bone homeostasis. Nox4(-/-) mice displayed higher bone density and reduced numbers and markers of osteoclasts. Ex vivo, differentiation of monocytes into osteoclasts with RANKL and M-CSF induced Nox4 expression. Loss of NOX4 activity attenuated osteoclastogenesis, which was accompanied by impaired activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
132
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(149 citation statements)
references
References 40 publications
7
132
1
Order By: Relevance
“…4). Although there are disagreements from a recent study using global Nox4 knock-out animal (30), cell type-specific conditional knock-out animal models may be used to untangle this possibility. However, in the current study, we used an ex vivo cell culture model and determined that knocking down Nox4 in cells from p47 phoxϪ/Ϫ mice blocked temporal osteoblastic cell differentiation signaling.…”
Section: Discussionmentioning
confidence: 99%
“…4). Although there are disagreements from a recent study using global Nox4 knock-out animal (30), cell type-specific conditional knock-out animal models may be used to untangle this possibility. However, in the current study, we used an ex vivo cell culture model and determined that knocking down Nox4 in cells from p47 phoxϪ/Ϫ mice blocked temporal osteoblastic cell differentiation signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Nox4 knockout animals have higher bone density, a phenotype that is likely caused by impaired formation and activation of osteoclasts [49]. In a murine model of postmenopausal osteoporosis, pharmacological or genetic inhibition of Nox4 reduced the loss of trabecular bone [49].…”
Section: Nox4mentioning
confidence: 99%
“…Recently, Goettsch et al 4 identified nicotinamide adenine dinucleotide phosphate oxidase 4 (NOX4) as a potential target for the treatment of osteoporosis. The nicotinamide adenine dinucleotide phosphate oxidases represent a family of enzymes that solely produce reactive oxygen species (ROS).…”
Section: 2mentioning
confidence: 99%
“…Goettsch et al 4 identified NOX4 as the relevant enzymatic source of ROS during bone metabolism and analyzed the mechanisms of osteoclastogenesis induced by ROS.…”
Section: -10mentioning
confidence: 99%